PENDAMPINGAN GURU MGMP MATEMATIKA OGAN KOMERING ILIR DALAM MERANCANG ASSESSMENT BERBASIS PEMODELAN UNTUK MENUNJANG AKM PESERTA DIDIK - Hartono, Yusuf; Hiltrimartin, Cecil; Araiku, Jeri; Nuraeni, Zuli; Kurniadi, Elika (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. Mathematical modeling is the process of mathematizing real-life problems into mathematical language. Modeling assessment is conducted to evaluate student learning outcomes at the end of the learning process and to gather information on students’ abilities, guiding teaching strategies. The lack of teacher competence in preparing mathematical modeling assessments and students' struggles in mathematical modeling result from a lack of experience in connecting mathematical concepts with real-life problems. This service activity aims to provide training for mathematics teachers in developing assessments based on mathematical modeling to enhance students' AKM. It also aims to understand the response of MGMP mathematics teachers to the training and to obtain high-quality learning tools based on mathematical modeling. The model for implementing this activity is a mentoring model designed to enhance teacher professionalism in preparing teaching and learning activities, particularly in creating digitally assisted learning tools. A total of 22 participants from Ogan Komering Ilir Regency took part in this activity, conducted synchronously and asynchronously. The analysis of the satisfaction response questionnaire revealed positive results in terms of relevance, material attractiveness, practicality, program design, feedback, and recommendations. Abstrak. Pemodelan matematika merupakan proses matematisasi dari permasalahan kehidupan nyata menjadi bahasa matematika. Asesmen pemodelan dilakukan untuk mengetahui hasil pembelajaran siswa di akhir pembelajaran dan juga untuk mendapatkan informasi kemampuan siswa agar bisa menentukan tindakan dalam mengajar siswa. Kurangnya kompetensi guru dalam menyusun asesmen pemodelan matematika dan kelemahan siswa dalam pemodelan matematika dikarenakan kurangnya pengalaman dalam menghubungkan konsep-konsep matematika pada permasalahan kehidupan nyata. Kegiatan pengabdian ini memiliki tujuan yaitu memberikan pelatihan kepada guru matematika dalam mengembangkan asesmen berbasis pemodelan matematika untuk menunjang AKM peserta didik, mengetahui respon guru-guru MGMP matematika terhadap pelatihan, serta mendapatkan perangkat pembelajaran berbasis pemodelan matematika yang berkualitas. Model pelaksanaan kegiatan ini adalah model pendampingan berkelompok untuk meningkatkan profesionalisme guru dalam mempersiapkan kegiatan belajar mengajar khususnya dalam membuat perangkat pembelajaran yang berbantuan digital. Jumlah peserta yang menghadiri kegiatan ini sebanyak 22 orang peserta dari Kabupaten Ogan Komering Ilir yang dilakukan secara synchronous dan asynchronous. Hasil analisis angket respon kepuasan mendapatkan hasil yang positif dari aspek relevansi, daya tarik materi, kepraktisan, desain program, umpan balik, hingga rekomendasi.